Dampak Sosial Media Terhadap Pembelajaran dan Interaksi Siswa - Nur Riswandy Marsuki; Muhamaad Saifullah; Nurdin Nurdin (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
The ever-growing digital era has made social media an integral part of everyday life, including among students. Social media now serves not only as a platform for socializing, but also as a potential learning tool inside and outside the classroom. However, even though it has positive potential, the use of social media in education also brings various problems and challenges. Some of the problems that arise include the impact on the quality of student learning, such as digital addiction, attention disorders, and the validity and security of information obtained from social media. This research aims to explore the impact of social media on the learning process and student interactions, as well as to identify effective strategies that can be used to utilize social media to improve the quality of education, while managing existing risks. This study also aims to provide insight into the integration of social media in existing educational curricula. By understanding the impact of social media holistically, it is hoped that educators and policy makers can develop appropriate guidelines to maximize the benefits of social media and minimize its potential risks, thereby contributing to the development of education that is adaptive and responsive to the challenges of the digital age.